Aerodynamic and Acoustic Simulations of Thick Flatback Airfoils Employing High Order DES Methods. Issue 8 (12th May 2022) - Bangga, Galih; Seel, Ferdinand; Lutz, Thorsten; Kühn, Timo
Abstract: The results of high fidelity aerodynamic and acoustic computations of thick flatback airfoils are reported in the present paper. The studies are conducted on a flatback airfoil having a relative thickness of 30% with the blunt trailing edge thickness of 10% relative to chord. Delayed Detached‐Eddy Simulation (DDES) approaches in combination with high order (5th) flux discretization WENO (Weighted Essentially Non‐Oscillatory) and l 2 R o e l^2Roe Riemann solver are employed. Two variants of the DES length scale calculation methods are compared. The results are validated against experimental data with good accuracy. The studies provide guideline on the mesh and turbulence modeling selection for flatback airfoil simulations. The results indicate that the wake breakdown is strongly influenced by the spanwise resolution of the mesh, which directly contributes to the prediction accuracy especially for drag force and noise emission. The Reynolds normal stress u ′ u ′ ¯ u^′ u^′ and the u ′ v ′ ¯ u^′ v^′ Reynolds stress component have the largest contributions on the mixing process, while the contribution of the u ′ w ′ ¯ u^′ w^′ component is minimal. Proper orthogonal decomposition is further performed to gain deeper insights into the wake characteristics. Abstract : Coherent wake structures are responsible for the noise tonality of flatback airfoils. High fidelity computational fluid dynamics (CFD) computations and flow field decompositions are employed to investigate this phenomenon in detail. The results can be used as a starting point for developing dedicated tonal noise reduction control for flatback airfoils.